2017
DOI: 10.31018/jans.v9i2.1353
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of change in cervical and shoulder posture due to carriage of different weight of backpack

Abstract: Present experimental research was planned to measure the percentage change in angle of cervical and shoulder posture of students due to carriage of different weights of backpack. For the above purpose total 30 students (15 boys and 15 girls) from the CBSE affiliated school of Meerut were selected by using the random and purposive sampling method. All the students were from the 7th class and belonged to the age group of 10-13 years. To measure the percentage change in cervical and spinal angle in terms of exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It is recommended that children carry school backpacks weighing no more than 8% of their body mass in order to prevent decreased CVA. Malik et al (2017), India The overall and anteroposterior proprioception indices were significantly higher when loaded with the traditional backpack as com pared to no load and to the double-sided bag (p < 0.05). The mediolateral proprioception index was significantly higher when carrying the traditional backpack load and the double-sided bag compared to no load (p < 0.05).…”
Section: Goswami Et Al (2017) Indiamentioning
confidence: 96%
See 1 more Smart Citation
“…It is recommended that children carry school backpacks weighing no more than 8% of their body mass in order to prevent decreased CVA. Malik et al (2017), India The overall and anteroposterior proprioception indices were significantly higher when loaded with the traditional backpack as com pared to no load and to the double-sided bag (p < 0.05). The mediolateral proprioception index was significantly higher when carrying the traditional backpack load and the double-sided bag compared to no load (p < 0.05).…”
Section: Goswami Et Al (2017) Indiamentioning
confidence: 96%
“…The 14 studies comprised 13 experimental, observational and cross-sectional studies, without concurrent controls (Abrahams et al 2011;Goswami, Sarkar & Mishra 2017;Hande et al 2012;Hundekari et al 2013;Khallaf et al 2016;Kistner et al 2013;Leman, Idris & Murdana 2013;Malik, Vinay & Pandey 2017;Mo et al 2013;Mosaad & Abdelaziem 2018;Pahwa 2013;Ramprasad, Alias & Raghuveer 2009;Vaghela et al 2019) and one experimental study with a concurrent control (Misra, Nigm & Alagesan 2012). Whilst all studies (n = 14) reviewed the effects of backpack loading on cervical posture, four included interventions (Leman et al 2013;Misra et al 2012;Mo et al 2013;Mosaad & Abdelaziem 2018) (Table 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A significant proportion of the available literature is based on data from the Northern Hemisphere (~88%), especially Europe (~48%), where sociodemographic and economic factors are considerably different to those in South Africa [ 34 ]. Therefore, substantially higher loads in the present study may be accounted for, at least partially, by factors such as access to lockers, security, quality of education, and quantity of homework [ 35 , 36 , 41 ]. The literature also showed that most schoolchildren within comparable age ranges tend to carry absolute loads of 5–7 kg [ 2 ] that fall within the acceptable 10–15% BM range.…”
Section: Discussionmentioning
confidence: 99%
“…All data are reported as mean ± SD unless otherwise stated. For the first objective, a nonparametric ANOVA (Kruskal–Wallis) was completed once all assumptions were checked (normality (Shapiro–Wilk), equality of variance (Levene)) to evaluate age-related differences in relative load carriage [ 36 ]. The post hoc Holm correction was used to adjust for multiple between-group comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…The incorrect use of the backpack with the load distributed asymmetrically causes the body to become unbalanced and requires load compensation. Thus, the adolescent who performs the behavior of using the backpack with only one of the straps or another way that is not with equal weight distribution on both shoulders may develop a postural change in the future (Kasović et al, 2018;Malik et al, 2017;Mosaad & Abdel-aziem, 2018).…”
Section: Discussionmentioning
confidence: 99%